Effects of previous exposure to different medications on the clinical course of COVID-19 patients in Istanbul, Turkey: Chronic drug use and COVID-19 - SUR ÜNAL, ÜLKÜ; YANANLI, HASAN RACİ (My University, 2023)
Background/Aim: Multiple studies have investigated the effects of drugs that alter ACE2 expression, such as renin-angiotensin system inhibitors, non-steroidal anti-inflammatory drugs, and thiazolidinediones, on the clinical course of coronavirus disease-2019 (COVID-19). But a consensus has not yet been reached, and it has been stated that they do not have any effect. There are publications in which metformin is associated with low mortality and insulin with high mortality. Data from different parts of the world are important given that the rate of spread of COVID-19 may be related to the expression status of ACE2 or TMPRSS2 receptors or some other unknown genetic factors. This study aims to examine the effects of medications used chronically in the last 6 months before contracting COVID-19 on the clinical course of COVID-19 in a sample of Istanbul, Turkey. Methods: In this retrospective cohort study, which included 525 patients diagnosed with COVID-19 between March and November 2020 from four family health centers in Istanbul, the records of the patients were retrospectively analyzed. In addition to demographic information, all medications chronically used by the patients in the last 6 months before the diagnosis of COVID-19 were noted. The effects of demographic data and medications on the three main endpoints of the study, which were hospitalization, intensive care unit (ICU) admission, and mortality, were analyzed using logistic regression models. Results: Of the 525 COVID-19 patients included in the study, 109 (20.8%) were hospitalized, 18 (3.4%) were treated in ICU, and 11 (2.1%) patients died. Increasing age is associated with hospitalization, ICU admission and mortality. Also, the presence of COVID-19 thoracic computed tomography (CT) findings and polypharmacy was associated with increased hospitalization. Living alone and the presence of COVID-19 thoracic CT findings was associated with increased ICU admission. When adjusted for age and comorbidity, logistic regression models revealed that medications for diabetes mellitus (DM) increased the probability of hospitalization (OR: 3.9, 95% CI 1.2-13.0), and calcium channel blockers (CCBs) increased the probability of ICU admission (OR: 15.8, 95% CI 2.1–120.2) and mortality (OR: 295.1, 95% CI 4.6– 18946.6). Conclusion: Previous use of DM medications and CCBs may negatively affect the clinical course of COVID-19.
Keywords: COVID-19; SARS-CoV-2; epidemiology; pharmacoepidemiology; hypoglycemic agents; calcium channel blockers